Dakwah Jurnalis TvOne: Studi Komunikasi Profetik dalam Pemberitaan Aksi Bela Palestina - Nappisah, Nappisah (Prodi Komunikasi & Penyiaran Islam, Program Pascasarajana, UIN Sunan Gunung Djati Bandung, 2018)
This study aims to describe the application of three main elements in prophetic journalism—humanization (amar ma'ruf), liberation (nahi munkar), and transcendence (tu'minu billah)—in the coverage of the Palestine-Israel conflict. Using a qualitative approach, constructivist paradigm, and phenomenological method, this research examines the role of media, particularly television, in educating the public and shaping public opinion regarding the Palestine issue. The Palestine Solidarity Action, supported by various parties including the media, serves as an important platform to provide support for the Palestinian people's struggle. This study is expected to provide a deeper understanding of how prophetic journalism can prioritize moral, ethical, and humanitarian values in news coverage. Keywords: Prophetic Communication, Journalists, TvOne, Palestinine Solidarity Action